Metal-doped carbon dots for simulating peroxidase as well as preparation method and application of metal-doped carbon dots

By preparing metal-doped carbon dots of simulated peroxidase, the problem of insufficient catalytic activity of existing nanoenzymes under different pH environments is solved, and the use of bacterial endogenous H2O2 in normal pH environments is achieved to exert excellent antibacterial properties.

CN119505888APending Publication Date: 2025-02-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311079602.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The catalytic activity of existing nanoenzymes is susceptible to external factors pH, and it is necessary to exert good antibacterial effects under the conditions of weak acid or the addition of exogenous H2O2.

Method used

By providing a preparation method that simulates peroxidase metal-doped carbon dots, metal-doped carbon dots with stronger catalytic properties and antibacterial activity are prepared by heating using a mixed reaction system of amino acids and transition metal salts.

Benefits of technology

This metal-doped carbon dot can effectively exert antibacterial performance under normal pH environment, and use bacterial endogenous H2O2 to achieve excellent antibacterial effects, avoiding dependence on external pH and H2O2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505888A_ABST
    Figure CN119505888A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-doped carbon dot for simulating peroxidase and a preparation method and application thereof, the preparation method comprises the following steps: providing a mixed reaction system containing amino acid and transition metal salt, heating the mixed reaction system to enable the amino acid and the transition metal salt to react, and preparing the metal-doped carbon dots for simulating peroxidase. The metal-doped carbon dots for simulating peroxidase prepared by the invention show good enzyme catalytic characteristics and antibacterial activity, and can show excellent antibacterial performance in a normal pH environment without adding H2O2; amino acid required by a human body is taken as a raw material, and the product prepared through simple reaction has the advantages of no toxicity, good biocompatibility, good water solubility, small size, uniformity and low preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano antibacterial materials, and specifically relates to a peroxidase-simulating metal-doped carbon dot and a preparation method and application thereof. Background Art

[0002] Bacteria are everywhere in human life and production. Acute and chronic diseases caused by bacteria are a constant threat to human health and safety, and are a public health safety issue faced by the world. Since the introduction of antibiotics into clinical treatment, countless lives have been saved. However, due to excessive and improper use of antibiotics, many pathogens have developed drug resistance. Data from the World Health Organization (WHO) show that by 2050, the number of deaths caused by bacterial infections will increase to 10 million.

[0003] The mechanisms of bacterial resistance mainly include the production of enzymes that inactivate antibiotics, the expression of efflux pumps, and the change of antibiotic recognition sites. They are resistant to multiple antibiotics at the same time. Nanomaterials act by directly contacting the bacterial cell wall without penetrating the cell; therefore, nanomaterials are not as likely to promote bacterial resistance as antibiotics. Therefore, in order to solve the limitations of traditional antibiotics and the current challenges of antibiotic resistance, a promising direction is antibiotic-free nanotechnology to develop new antibacterial agents to achieve better antibacterial effects.

[0004] As a new type of quasi-spherical luminescent nanomaterial, carbon-based nanomaterials provide a new idea for the research and development of new antibacterial materials. Its typical size is 10nm or less, and it has the advantages of simple synthesis, small particle size, low cost, good water dispersibility, adjustable fluorescence, low cytotoxicity, and good biocompatibility. Metal-doped carbon dots combine metal ions with the good electron mobility of CDs, change the charge density and charge transfer form between metal ions and CDs, and are expected to regulate the physicochemical properties of CDs to a greater extent, causing new physicochemical properties of CDs, such as catalytic properties. Metal-doped carbon dot nanozymes can further destroy cell components / biofilms or interfere with bacterial DNA synthesis by exerting enzyme catalytic properties to change the level of reactive oxygen, thereby enhancing bactericidal ability. However, the catalytic activity of nanozymes is easily affected by external factors such as pH, and it needs to be in weak acid or exogenous H2O2 conditions to exert good antibacterial effects. Therefore, it is urgent to provide a metal-doped carbon dot that can exhibit excellent antibacterial properties under normal pH conditions. Summary of the invention

[0005] The present invention provides a peroxidase-simulated metal-doped carbon dot and a preparation method and application thereof, aiming to solve the technical problem in the prior art that the catalytic activity of nanozymes is easily affected by external factors pH and requires weak acid or exogenous H2O2 conditions to exert a good antibacterial effect.

[0006] In order to achieve the above technical effects, the technical solution adopted by the present invention is as follows:

[0007] The present invention provides a simulated peroxidase metal-doped carbon dot and a preparation method and application thereof. The preparation method comprises providing a mixed reaction system containing amino acids and transition metal salts, heating the mixed reaction system so that the transition metal is chelated into the amino acids, and obtaining the simulated peroxidase metal-doped carbon dot through carbonization.

[0008] Furthermore, the amino acids include any one or more combinations of 20 amino acids required by the human body, including glycine, alanine, valine, leucine, isoleucine, methionine (methionine), proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine.

[0009] Furthermore, the amino acid includes any one of arginine, lysine and histidine.

[0010] Furthermore, the transition metal salt includes any one of inorganic compounds of iron, manganese, cobalt, nickel, copper, zinc and cerium.

[0011] Furthermore, the molar ratio of the amino acid to the transition metal salt is 1:0.01-10.

[0012] Furthermore, the preparation method includes providing a mixed reaction system containing an amino acid and a transition metal salt, stirring the mixed reaction system so that the mixed reaction system is in a clarified state, and then heating the mixed reaction system so that the amino acid and the transition metal salt react to obtain the simulated peroxidase metal-doped carbon dots.

[0013] Furthermore, the heating method includes microwave heating, hydrothermal heating and other common heating methods. The heating method is not limited. Preferably, microwave heating is used with a heating power of 400-700W and heating for 3-10 minutes.

[0014] Furthermore, the molar ratio of the amino acid to the transition metal salt is 1:0.1.

[0015] Furthermore, the transition metal salt includes any one of iron salt, copper salt, cobalt salt and cerium salt, or a combination of two or more thereof.

[0016] Furthermore, the preparation method further comprises passivating the prepared simulated peroxidase metal-doped carbon dots, filtering with a 0.22 μm microporous filter membrane, using deionized water as the dialysate, dialysis treatment at 1000-2000 Da for 48 hours, and then freeze-drying.

[0017] The simulated peroxidase metal-doped carbon dots are prepared by the preparation method provided by the invention.

[0018] Furthermore, the above-mentioned simulated peroxidase metal-doped carbon dots are spherical, with a particle size of 2-3 nm, and a metal element doping amount of 0.5-6.0 wt%.

[0019] Furthermore, when the concentration of the simulated peroxidase metal-doped carbon dots was 5 μg / mL, the inhibition rate against Staphylococcus aureus reached 99%.

[0020] The simulated peroxidase metal-doped carbon dots prepared by the preparation method provided by the present invention are used in the fields of antibacterial and sterilization.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The metal-doped carbon dots prepared in the present invention exhibit better simulated peroxidase catalytic properties and antibacterial activity.

[0023] 2. The metal-doped carbon dots prepared by the preparation method of the present invention avoid the deficiency that general nanomaterials simulating peroxidase properties need to be in a weak acid environment or with the assistance of exogenous H2O2 to exert their antibacterial effects. In a normal pH environment, the metal-doped carbon dots prepared by the preparation method of the present invention can exhibit excellent antibacterial properties by utilizing endogenous H2O2 of bacteria.

[0024] 3. The preparation method provided by the present invention is simple, easy to promote, has a short reaction time, does not require experimental conditions such as high-temperature calcination, and uses amino acids as raw materials. The prepared metal-doped carbon dots are non-toxic, have good water solubility, low cost, good biocompatibility, and are small and uniform in size.

[0025] 4. When the concentration of the simulated peroxidase metal-doped carbon dots prepared by the present invention is 5 μg / mL, the antibacterial rate against Staphylococcus aureus reaches 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1a This is a transmission electron micrograph of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0028] Figure 1b This is a particle size distribution diagram of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0029] Figure 2 This is the infrared spectrum of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0030] Figure 3 This is an X-ray photoelectron spectrum of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0031] Figure 4a This is a curve diagram showing the relationship between the absorbance of the metal-doped carbon dot material prepared in Example 1 of the present invention and the concentration of hydrogen peroxide.

[0032] Figure 4b This is a curve diagram of the determination of the peroxidase-like Michaelis constant of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0033] Figure 5a This is a diagram of antibacterial flat plate coating with different concentrations of metal-doped carbon dot materials prepared in Example 1 of the present invention.

[0034] Figure 5b This is a graph showing the antibacterial performance test results of the metal-doped carbon dot material at different concentrations prepared in Example 1 of the present invention.

[0035] Figure 6a This is a diagram of antibacterial flat plate coating with different concentrations of metal-doped carbon dot materials prepared in Comparative Example 1 of the present invention.

[0036] Figure 6b This is a graph showing the antibacterial performance test results of different concentrations of the metal-doped carbon dot material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The present invention will be more fully understood through the following detailed description, which should be read in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are only exemplary of the present invention, which can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis of the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in virtually any appropriate detailed embodiment.

[0038] Unless otherwise specified, the reagents used in the present invention can be purchased from conventional biochemical reagent companies.

[0039] Example 1

[0040] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0041] 1.46 g of lysine and 0.17 g of CuCl2·2H2O were dissolved in 30 mL of deionized water and ultrasonicated for 5 min to make the mixed aqueous solution clear. Subsequently, the mixed aqueous solution was placed in a microwave oven and heated at a power of 700 W for 5 min to obtain a caramel-like black-brown solid. The above black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous filter membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, i.e., Cu-doped carbon dots, which was stored at room temperature.

[0042] Example 2

[0043] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0044] 1.74 g of arginine and 0.17 g of CuCl2·2H2O were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. The mixed aqueous solution was clarified, and then the mixed aqueous solution was placed in a microwave oven and heated at 700 W for 5 min to obtain a caramel-like black-brown solid. The black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Cu-doped carbon dots, and stored at room temperature.

[0045] Example 3

[0046] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0047] 1.47 g of glutamic acid and 16.2 g of FeCl3 were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. The mixed aqueous solution was clarified, and then the mixed aqueous solution was placed in a microwave oven and heated at 700 W for 5 min to obtain a caramel-like black-brown solid. The black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Fe-doped carbon dots, and stored at room temperature.

[0048] Example 4

[0049] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0050] 1.55 g of histidine and 0.162 g of FeCl3 were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. The mixed aqueous solution was clarified, and then the mixed aqueous solution was placed in a microwave oven and heated at 700 W for 5 min to obtain a caramel-like black-brown solid. The black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Fe-doped carbon dots, and stored at room temperature.

[0051] Example 5

[0052] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0053] 1.33 g of aspartic acid and 0.238 g of CoCl3·6H2O were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. The mixed aqueous solution was clarified, and then the mixed aqueous solution was placed in a microwave oven and heated at 700 W for 5 min to obtain a caramel-like black-brown solid. The black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous filter membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Co-doped carbon dots, and stored at room temperature.

[0054] Example 6

[0055] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0056] 2.04 g of tryptophan and 0.238 g of CoCl3·6H2O were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. Subsequently, the aqueous solution was placed in a microwave oven and heated at 700 W for 3-10 min to obtain a caramel-like black-brown solid, which was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous filter membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 500-1000 Da) for 24-48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Co-doped carbon dots, and stored at room temperature.

[0057] Example 7

[0058] This embodiment provides a peroxidase-simulating metal-doped carbon dot. Specifically, the preparation process includes:

[0059] 1.74 g of arginine and 0.0434 g of Ce(NO3)3·6H2O were dissolved in 30 mL of deionized water and ultrasonicated for 5 min. The mixed aqueous solution was clarified, and then the mixed aqueous solution was placed in a microwave oven and heated at 700 W for 5 min to obtain a caramel-like black-brown solid. The black-brown solid was dissolved in 20 mL of deionized water and filtered with a 0.22 μm microporous filter membrane to remove insoluble matter, and then dialyzed in water (molecular weight cutoff: 1000 Da) for 48 h. The dialyzed product was concentrated by freeze drying to obtain a brown solid powder, which was Ce-doped carbon dots, and stored at room temperature.

[0060] Performance Characterization

[0061] Morphological characteristics

[0062] The morphology of the copper-doped carbon dot material prepared in Example 1 was observed under a transmission electron microscope. Figure 1a , it can be seen that its surface is dense and flat, and the copper-doped carbon dots are spherical; Figure 1b This is a particle size distribution diagram of the metal-doped carbon dot material prepared in Example 1 of the present invention. The particle size of the prepared copper-doped carbon dots is 2.14 nm, and the copper doping amount is 6.0 wt %.

[0063] The copper doping amount of the copper-doped carbon dot material prepared in Example 2 is 3.85wt%, the iron doping amount of the iron-doped carbon dot material prepared in Example 4 is 2.55wt%, the cobalt doping amount of the cobalt-doped carbon dot material prepared in Example 5 is 2.135wt%, and the cerium doping amount of the cerium-doped carbon dot material prepared in Example 7 is 0.5wt%.

[0064] See also Figure 2 , is the infrared spectrum of the metal-doped carbon dot material prepared in Example 1 of the present invention, showing CD and CuCD characteristic peaks.

[0065] See also Figure 3 , is the X-ray photoelectron spectrum of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0066] Enzyme activity performance test

[0067] Simulated catalase performance test: The copper-doped carbon dots (500 μg / mL) prepared in Example 1 were weighed and quantified and dissolved in acetic acid-sodium acetate buffer (pH 4.5, 20 mM), 10 mM tetramethylbenzidine (TMB) was added, and then H2O2 (10 mM) was added. After being fully mixed for 30 min, the color of the solution gradually turned blue due to the generation of reactive oxygen hydroxyl radicals to oxidize TMB to develop color, proving that the copper-doped carbon dots have the characteristics of simulating catalase, see Figure 4a , Figure 4b ,in Figure 4aThis is a curve diagram showing the relationship between the absorbance (at 652 nm) of the metal-doped carbon dot material prepared in Example 1 of the present invention and the concentration of hydrogen peroxide. It can be seen that the absorbance of the metal-doped carbon dot material prepared in Example 1 increases with the increase of the concentration of hydrogen peroxide; Figure 4b This is a curve diagram of the determination of the peroxidase-like Michaelis constant of the metal-doped carbon dot material prepared in Example 1 of the present invention.

[0068] Antibacterial performance test

[0069] A single colony was picked from the plate and placed in 3 mL of LB medium. The culture was incubated overnight at 37°C with a constant temperature shaker at 180 rpm for 18 h. Then 100 μL of the bacterial solution was diluted to 3 mL of LB medium. The colony was activated by shaking at 37°C with a constant temperature shaker at 180 rpm for 4 h. The bacterial concentration was measured by the OD value to be 10 8 CFU / mL, and the above bacteria were further diluted 10 3 The incubated bacteria were diluted 100 times and 100 μL was used for agar plate coating and placed at 37 °C for 12 h. Figure 5a , Figure 5b As shown, Figure 5a The antibacterial graph of different concentrations of metal-doped carbon dots prepared in Example 1 of the present invention, from left to right, the concentrations of copper-doped carbon dots are 0 (blank control group), 5, 10, 25, 50, 100 μg / mL (using Staphylococcus aureus as a model); Figure 5b The antibacterial performance of copper-doped carbon dots with different concentrations is shown in Figure 2. When the concentration of copper-doped carbon dots is 0, the number of bacteria is as high as 3.875×10 6 CFU / mL, when copper-doped carbon dots were added, the number of bacteria was greatly reduced. When the concentrations of copper-doped carbon dots were 5 and 10 μg / mL, there were still a small number of bacteria. When the concentrations of copper-doped carbon dots were 25 and 50 μg / mL, there were almost no bacteria. When the concentration of copper-doped carbon dots was 100 μg / mL, no bacteria survived.

[0070] Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 1 is that CuCl2·2H2O is not added in Comparative Example 1, and the other conditions are the same as those in Example 1.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 4 is that FeCl3 is not added in Comparative Example 2, and the other conditions are consistent with Example 4.

[0074] The simulated peroxidases prepared in Examples 1-6 and Comparative Examples 1-2 were tested for their antibacterial properties using the above-mentioned antibacterial property test method, and the number of bacteria when the simulated peroxidase concentration was 5 μg / mL was compared. The specific results are tabulated as follows:

[0075] Table 1 Comparison of bacterial counts when the concentration of simulated peroxidase prepared in Examples 1-6 and Comparative Examples 1-3 is 5 μg / mL

[0076]

[0077]

[0078] The data in the above table show that the copper-doped carbon dots prepared in Example 1 by adding CuCl2·2H2O have a much greater inhibitory ability against Staphylococcus aureus at a concentration of 5 μg / mL than Comparative Example 1. Similarly, the iron-doped carbon dots prepared in Example 4 have a much greater inhibitory ability against Staphylococcus aureus at a concentration of 5 μg / mL than Comparative Example 2.

[0079] In summary, the present invention provides a simulated peroxidase metal-doped carbon dot and a preparation method and application thereof. The preparation method comprises: providing a mixed reaction system containing an amino acid and a transition metal salt, heating the mixed reaction system to allow the amino acid and the transition metal salt to react, and then carbonizing the metal to chelate the functional groups on the amino acid to obtain the simulated peroxidase metal-doped carbon dot.

[0080] The metal-doped carbon dots prepared by the present invention exhibit better simulated peroxidase catalytic properties and antibacterial activity. The metal-doped carbon dots prepared by the preparation method of the present invention avoid the disadvantage that the general nanomaterials simulating peroxidase properties need to be in a weak acid environment or with the assistance of exogenous H2O2 to exert antibacterial effects. In a normal pH environment, the metal-doped carbon dots can exhibit excellent antibacterial properties by utilizing endogenous H2O2 of bacteria.

[0081] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

Claims

1. A method for preparing metal-doped carbon dots simulating peroxidase, characterized in that: The method comprises providing a mixed reaction system containing amino acids and transition metal salts, heating the mixed reaction system so that the transition metal is chelated into the amino acids, and carbonizing to obtain the simulated peroxidase metal-doped carbon dots.

2. The method for preparing the simulated peroxidase metal-doped carbon dots according to claim 1, characterized in that: The mixed reaction system is stirred to a clear state and then heated to allow the amino acid and the transition metal salt to react to obtain the simulated peroxidase metal-doped carbon dots.

3. The method for preparing the simulated peroxidase metal-doped carbon dots according to claim 2, characterized in that: Heating the mixed reaction system to chelate the transition metal into the amino acid includes using microwave heating with a power of 400-700 W for 3-10 minutes.

4. The method for preparing the simulated peroxidase metal-doped carbon dots according to claim 3, characterized in that: The amino acids include any one or more of glycine, alanine, valine, leucine, isoleucine, methionine, proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine; and / or, the molar ratio of the amino acid to the transition metal salt is 1:0.01-10; And / or, the transition metal salt includes any one of inorganic compounds of iron, cobalt, nickel, copper, zinc and cerium.

5. The method for preparing the simulated peroxidase metal-doped carbon dots according to claim 4, characterized in that: The amino acid includes any one of arginine, lysine, and histidine; and / or, the molar ratio of the amino acid to the transition metal salt is 1:0.1; And / or, the transition metal salt includes any one of iron salt, copper salt, cobalt salt and cerium salt, or a combination of two or more thereof.

6. The method for preparing the simulated peroxidase metal-doped carbon dots according to claim 3, characterized in that: The method also includes filtering, dialysis and freeze-drying the prepared simulated peroxidase metal-doped carbon dots.

7. The simulated peroxidase metal-doped carbon dots obtained by the preparation method according to any one of claims 1 to 6.

8. The peroxidase-mimicking metal-doped carbon dots according to claim 7, characterized in that: The simulated peroxidase metal-doped carbon dots are spherical, with a particle size of 2-3 nm and a metal element doping amount of 0.5-6.0 wt %.

9. The peroxidase-mimicking metal-doped carbon dots according to claim 8, characterized in that: When the concentration of the simulated peroxidase metal-doped carbon dots is 5 μg / mL, the antibacterial rate against Staphylococcus aureus reaches 99%.

10. Use of the peroxidase-mimicking metal-doped carbon dots as claimed in claim 8 or 9 in the field of antibacterial and sterilization.

Citation Information

Cited By

  • Nickel-doped histidine carbon nano enzyme and preparation method thereof

    CN119701962A